The major's daughter [large type] - Jennings, Regina (Regina Lea) (Jennings, Regina (Regina Lea). Fort Reno series, 2019)
"Caroline Adams returns to Indian Territory after tiring of confining society life. She wants adventure, and when she and her friend Amber come across swaggering outlaw Frisco Smith, they find his dreams for the new territory are very persuasive. With the much-anticipated land run pending, they may just join the rush. Growing up parentless, all Frisco Smith wanted was a place to call his own. It's no wonder that he fought to open the Unassigned Lands. After years of sneaking across the border, he's even managed to put in a dugout house on a hidden piece of property he's poised to claim. When the gun sounds, everyone's best plans are thrown out the window in the chaos of the run. Caroline and Frisco soon find themselves battling over a claim--and both dig in their heels. Settling the rightful ownership will bring these two closer than they ever expected and change their ideas of what a true home looks like"--